Synthetic routes contaminate graphene materials with a whole spectrum of unanticipated metallic elements - Wong, Colin Hong An; Sofer, Zdeněk; Kubešová, Marie; Kučera, Jan; Matějková, Stanislava; Pumera, Martin (Proceedings of the National Academy of Sciences of the United States of America, 2014)
The synthesis of graphene materials is typically carried out by oxidizing graphite to graphite oxide followed by a reduction process. Numerous methods exist for both the oxidation and reduction steps, which causes unpredictable contamination from metallic impurities into the final material. These impurities are known to have considerable impact on the properties of graphene materials. We synthesized several reduced graphene oxides from extremely pure graphite using several popular oxidation and reduction methods and tracked the concentrations of metallic impurities at each stage of synthesis. We show that different combinations of oxidation and reduction introduce varying types as well as amounts of metallic elements into the graphene materials, and their origin can be traced to impurities within the chemical reagents used during synthesis. These metallic impurities are able to alter the graphene materials' electrochemical properties significantly and have wide-reaching implications on the potential applications of graphene materials.